The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1365-2966.2010.17073.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular line profiles from contracting dense cores

Abstract: We recently proposed that molecular cloud dense cores undergo a prolonged period of quasistatic contraction prior to true collapse. This theory could explain the observation that many starless cores exhibit, through their spectral line profiles, signs of inward motion. We now use our model, together with a publicly available radiative transfer code, to determine the emission from three commonly used species -N 2 H + , CS and HCN. A representative dense core of 3 M that has been contracting for 1 Myr has line p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 54 publications
(88 reference statements)
4
17
0
Order By: Relevance
“…Eventually, all gas materials would continue to fall toward the center to form a protostellar core. This scenario is consistent with both theoretical (e.g., Stahler & Yen 2010) and observational (e.g., Lee & Myers 2011) pictures concerning the evolution of internal motions in starless cores.…”
Section: Conclusion and Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Eventually, all gas materials would continue to fall toward the center to form a protostellar core. This scenario is consistent with both theoretical (e.g., Stahler & Yen 2010) and observational (e.g., Lee & Myers 2011) pictures concerning the evolution of internal motions in starless cores.…”
Section: Conclusion and Discussionsupporting
confidence: 75%
“…Both theoretical (e.g., Broderick et al 2007;Stahler & Yen 2010) and observational (e.g., Lee & Myers 2011) works reveal that a static core would show expansive or oscillatory motions once perturbed on large scales. While a molecular cloud is undergoing an expansive or oscillatory mode on large scales, its core may begin to collapse or contract due to nonlinear instabilities under self-gravity.…”
Section: Introductionmentioning
confidence: 99%
“…We adopt values of n d = 2 × 10 4 cm −3 for the depletion density and A 0 = 4 × 10 −9 for the low-density abundance limit, based on the typical values given in Tafalla et al (2002). Stahler & Yen (2010) recently carried out line modeling of diffuse cores with and without CS depletion, and found that the models with depletion were a better match to observations, and so we adopt it here. Due to depletion, the number density of CS is almost negligible in the densest regions of our cores.…”
Section: Molecular Speciesmentioning
confidence: 99%
“…The study of spherical core line profiles has continued in more recent years. In particular, Rawlings & Yates (2001), Tsamis et al (2008), and Stahler & Yen (2010) have shown the importance of accurately modeling the chemical abundances within cores, particularly since optically thick carbon-bearing species, such as CO and CS, freeze out within the dense core centers (Tafalla et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As long as the temperature is low enough, CS and other sulphur-bearing molecules are expected to be strongly depleted towards the centre of dense cores where the density is high (e.g., Tafalla et al 2004;Bergin et al 2001). Depletion occurs due to the freezing-out process onto the dust grains (e.g., Tafalla et al 2002;Stahler & Yen 2010) and observations of starless cores, such as L1544, or Class 0 protostars, such as IRAM 04191, also showed CS depletion towards the centre by a factor of ∼20 Belloche et al 2002).…”
Section: Abundancementioning
confidence: 99%